Factors Affecting the Decision to Purchase Life Insurance Products in Vietnam - Tam, Phan Thanh (International Journal of Supply Chain Management, 2020)
In the current momentum of economic development, insurance increasingly demonstrates its essential role in socio-economic life. The critical part of insurance is financial service and social security mechanisms in the national economy. The life insurance product is a necessary product with both mental and physical value. Therefore, understanding life insurance’s meaning and benefits help customers have a positive outlook on life. Thus, the paper objective determines the factors affecting the decision to purchase life insurance products in Vietnam. The results showed five determinants: Benefit awareness, subjective standards, attitude towards life insurance, financial literacy, and access to the product. All five factors affected the intent and the decision to purchase life insurance products in Vietnam with 1% significance. Since then, the authors gave several recommendations to enhance the decision to buy life insurance products